Modelling and finite element simulation of martensite and bainite phase transformations during quenching under consideration of carbon repartitioning - Furlan, Tim; Schewe, Markus; Scherm, Philipp; Retzl, Philipp; Kozeschnik, Ernst; Menzel, Andreas (Mechanics of Materials, 2025)
Control of the microstructure of steel components during their processing is a crucial factor for reaching desired product properties. Realistic simulations of the microstructure evolution during processing can facilitate the improvement of existing processes as well as the design of new ones by reducing the need for time- and cost-intensive experimental investigations. This work focuses on the modelling and advanced simulation of quenching of components made of the high-carbon bearing steels 100Cr6 and 100CrMnSi6-4, during which transformations from austenite to martensite and bainite are considered. Special attention is given to the carbon-enrichment of the austenite phase during the formation of carbide-free bainite, since the change in carbon content also changes the martensite start temperature. A novel model based on the widely used Koistinen–Marburger and Johnson–Mehl–Avrami–Kolmogorov models is proposed, which explicitly takes into account the carbon contents of the remaining austenite and its influence on the kinetics of both transformations. The proposed model is implemented as a user material for the commercial finite element software Abaqus. Our source code and calibration data are available
Keywords: Phase transformations; Carbon repartitioning; High-carbon steel; Quenching; Abaqus; UMAT